Sod production and the effects of liquid organo-mineral fertilizers and thickness of sod - Lima, Claudinei Paulo de; Backes, Clarice; Marques Santos, Alessandro Jose; Villas Boas, Roberto Lyra [UNESP]; Fernandes, Dirceu Maximino [UNESP]; Grava de Godoy, Leandro Jose [UNESP]; Oliveira, Mauricio Roberto de [UNESP] (Univ Sao Paolo, 2018)
Nitrogen fertilization and an appropriate cutting thickness can result in firmer sod that can be handled in less time with greater turfgrass regrowth during the subsequent cycle. This experiment was conducted on a sod production farm located in Capela do Alto, in the state of Sao Paulo, Brazil. The soil was a dystrophic Rhodic Hapludox (Oxisol) with a medium texture. The experiment had two statistical designs; the initial design was randomized blocks with seven treatments and four replicates. Treatments were five doses of liquid organo-mineral fertilizer (OMF) corresponding to 0, 100, 200, 300 and 400 kg ha(-1) of nitrogen (N) with supplementation of phosphorous (P) and potassium (K) as well as two control treatments - one with 300 kg ha(-1) of N as OMF and the other with 300 kg ha(-1) of N-urea + P and K. At harvest, the adopted design was a split-plot type with four replicates in a 7 x 3 factorial arrangement with seven treatments as the main plot and three sod cutting heights (9, 16 and 22 mm) as subplots. Nitrogen doses in the form of OMF influenced the percentage of ground cover (PGC) by turfgrass in both cycles. The N dose of 300 kg ha(-1) formed the sod more quickly and provided the largest mass of roots and stolons and the highest sod tensile strength. The thinnest sod samples had faster regrowth and provided higher PGCs.
Keywords: Zoysia japonica Steud.; nitrogen fertilization; sod quality